2023
DOI: 10.3390/ijms24043554
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuropathy in Diabetes Mellitus: Pathogenetic Mechanisms and Diagnostic Options

Abstract: Diabetic neuropathy (DN) is one of the main microvascular complications of both type 1 and type 2 diabetes mellitus. Sometimes, this could already be present at the time of diagnosis for type 2 diabetes mellitus (T2DM), while it appears in subjects with type 1 diabetes mellitus (T1DM) almost 10 years after the onset of the disease. The impairment can involve both somatic fibers of the peripheral nervous system, with sensory-motor manifestations, as well as the autonomic system, with neurovegetative multiorgan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 160 publications
1
21
0
1
Order By: Relevance
“…In this study, the prevalence of PSN by VPT and DNE were 20.6 % and 35.6 % in T2DM patients and 2.8 % and 3.7 % in nondiabetic controls respectively. The prevalence of PSN in non-diabetic controls in our study is consistent with the report of peripheral neuropathies in the general population, which is within the range of 1 – 7 % [21] , and this has been attributed to alcoholism [22] , vitamin deficiency [23] , chronic exposure to recreational drugs and heavy metal [24] and medications [8] , [21] . The prevalence of PSN in T2DM patients in the current study is consistent with our previous studies in T2DM patients that reported the prevalence of PSN to be 15.2 % using VPT ≥ 25 [6] and 16.6 % using VPT > 97.5th percentile of age and gender-adjusted cut-off [17] .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In this study, the prevalence of PSN by VPT and DNE were 20.6 % and 35.6 % in T2DM patients and 2.8 % and 3.7 % in nondiabetic controls respectively. The prevalence of PSN in non-diabetic controls in our study is consistent with the report of peripheral neuropathies in the general population, which is within the range of 1 – 7 % [21] , and this has been attributed to alcoholism [22] , vitamin deficiency [23] , chronic exposure to recreational drugs and heavy metal [24] and medications [8] , [21] . The prevalence of PSN in T2DM patients in the current study is consistent with our previous studies in T2DM patients that reported the prevalence of PSN to be 15.2 % using VPT ≥ 25 [6] and 16.6 % using VPT > 97.5th percentile of age and gender-adjusted cut-off [17] .…”
Section: Discussionsupporting
confidence: 90%
“…The manifestations of PSN in diabetes patients depend on the type of nerve fibre involved (small or large) and the organs that these nerves supply. PSN may be presented as symmetric sensory-motor axonal neuropathy, proximal asymmetric painful motor neuropathy, mononeuropathy, and autonomic neuropathy which mainly involves small nerve fibres [8] , [6] . There have been several metabolic, inflammatory and cellular signalling defects have been postulated to underline the development of PSN in diabetes patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher prevalence of this complication is linked to an increased risk of diabetic neuropathy with advancing age. Age greater than 60 years is associated with a heightened risk of developing diabetic neuropathy due to biological aging processes such as alterations in nerve vasculature, increased advanced glycation end products, and decreased resistance to oxidative stress products [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Okamoto et al ( 30 ) indicated that the CMI of VZV in individuals with diabetes was significantly lower than that in healthy controls, which explains why people with diabetes are more likely to develop HZ. Persistent inflammation in patients with DM leads to nerve damage and increased pain sensitivity, which might contribute to the increased incidence of PHN in patients with DM ( 31 ). Ma et al ( 32 ) proposed that autoimmune pathogenesis resulted in impaired function of monocyte/macrophage in patients with T1DM.…”
Section: Discussionmentioning
confidence: 99%